2002
DOI: 10.1177/089198870201500205
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone and 9-Hydroxyrisperidone Concentrations Are Not Dependent on Age or Creatinine Clearance among Elderly Subjects

Abstract: Risperidone is extensively metabolized to an active metabolite, 9-hydroxyrisperidone (9-OH), which is dependent on renal clearance. Risperidone and 9-OH clearances are reduced in the elderly when compared to young subjects. The objective of this study was to determine whether among elderly subjects, risperidone and 9-OH clearance would further decline with increasing age and decreasing creatinine clearance (CrCl). Twenty geriatric inpatients were evaluated in a naturalistic setting with regard to total daily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In most previous studies (), an increase in dose‐adjusted concentrations has been found in the elderly, most often defined as those above 65 of 70 years of age, but the extent of this increase has varied considerably and there are also studies where no age‐related increases were found . In almost none of these studies, attempts have been made to divide the elderly into separate age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most previous studies (), an increase in dose‐adjusted concentrations has been found in the elderly, most often defined as those above 65 of 70 years of age, but the extent of this increase has varied considerably and there are also studies where no age‐related increases were found . In almost none of these studies, attempts have been made to divide the elderly into separate age groups.…”
Section: Discussionmentioning
confidence: 99%
“…For risperidone, no discernible influence of age on the dose‐adjusted plasma concentrations of risperidone plus its active metabolite 9‐hydroxyrisperidone was found in 95 samples from a therapeutic drug monitoring (TDM) service or in a study in 20 geriatric in‐patients . In contrast, another study found that the dose‐adjusted concentration of risperidone plus active metabolite was almost three‐fold higher in the age group above 60 than in those below 45 .…”
Section: Introductionmentioning
confidence: 96%
“…All PBPK models were verified in the elderly using published clinical data of 20 geriatric inpatients aged 55 years of age or older, admitted to the inpatient programs of the Western Psychiatric Institute and Clinic (3811 O'Hara Street, Pittsburgh, PAP 15213) between November 1996 and March 1998 (29). All patients were identified through daily reviews of pharmacy records, prescribed risperidone and treated under naturalistic conditions.…”
Section: Study Datamentioning
confidence: 99%
“…There are manifold reasons for this. Firstly, all geriatric inpatients enrolled in the published investigation were treated under naturalistic conditions (29). This means, potentially concomitant medication with CYP inhibitors or inducers should be considered, since patients over the age of 65 years often suffer from several diseases.…”
Section: Pbpk-based Phenotyping Using Metabolic Ratiomentioning
confidence: 99%
See 1 more Smart Citation